Коливальна спектроскопія комплексоутворення у водних розчинах ізопропанолу - Kutsyk, A. M.; Ilchenko, O. O.; Yuzvenko, Ya. M.; Obukhovsky, V. V.; Nikonova, V. V. (Publishing house "Academperiodika", 2018)
The formation of molecular complexes in isopropanol-water solutions is studied by means of vibrational spectroscopy techniques. The ATR FTIR spectra of solutions with different mixing ratios are detected. The multivariate curve resolution of the experimental data set shows that the investigated solution could be treated as a four-component mixture, which contains pure isopropanol, pure water, and two molecular complexes.